Sinusoidal movement of a grating across the monkey's fingerpad: representation of grating and movement features in afferent fiber responses - Goodwin, AW (J Neurosci, 1987)
Gratings of alternating grooves and ridges were moved sinusoidally back and forth across the monkey's fingerpad. Each grating was completely specified by its spatial period and the movement by its peak speed: together these determined the peak temporal frequency at which grating ridges passed over the skin. Responses of cutaneous, mechanoreceptive afferents innervating the fingerpad were characterized in terms of these 3 parameters. Slowly adapting afferents (SAs), rapidly adapting afferents (RAs), and Pacinian afferents (PCs) had different characteristics. The responses (mean cyclic discharge rates) of the SAs increased when the spatial period of the grating increased (and peak speed of movement remained constant) but did not change with changes in the peak speed of the movement (while the spatial period of the grating remained constant). Conversely, the responses of the PCs increased when the peak speed of movement increased (and the spatial period remained constant) but were relatively insensitive to changes in the spatial period of the grating (while the peak speed remained constant). The responses of the RAs increased as the spatial period of the grating increased (and peak speed remained constant) and also increased as the peak speed of movement increased (and the grating spatial period remained constant). When the peak temporal frequency of the grating ridges was held constant, the responses of all 3 afferent groups changed with changes in the grating spatial period or in the peak speed of movement. Information about the spatial features of the grating, independent of the peak speed of movement, was present in the SA population response and in the ratios of the RA and PC population responses. Information about the peak speed of movement, independent of the spatial period of the grating, was present in the PC population response and could be extracted from the RA population response.